Big lies : from Socrates to social media - Kurlansky, Mark (Tilbury House Publishers, 2022)
Writer Mark Kurlansky tackles the topic of pervasive lies and propaganda in social media and other information outlets and shows how it's nothing new. Individuals, governments, and institutions have lied throughout the centuries to avoid taking responsibility, cast blame, and gain power. Citing historical examples from the Middle Ages to the Salem witch trials to Hitler's propaganda about Jews, Kurlansky explains the tactics those in power used to sway public opinion. He also gives readers tools for looking critically at an argument or allegation, including using the scientific method and following the money trail to see who benefits. Sidebars, comic strips, illustrations, and photographs break up the text to highlight and supplement the information presented.